Risk perception of COVID-19, depressive symptoms and Internet addiction among undergraduates: a longitudinal study - Hongpo Zhang; Hongpo Zhang; Dandan Zhang; Wanghua Ji; Shun Peng (Frontiers in Public Health)
BackgroundThe COVID-19 pandemic has caused serious negative psychological effects worldwide, relatively little research has been performed on the potential enduring effects of COVID-19 on people’s emotional health and Internet addiction. This study was to examine the longitudinal associations between risk perception of COVID-19, depressive symptoms, and Internet addiction among Chinese undergraduates.MethodsWe conducted a two-wave longitudinal survey by convenience sampling, a total of 1,153 Chinese undergraduate students completed questionnaires measuring their COVID-19 risk perception and post-traumatic growth (PTG) in December 2022 (T1) via an online survey. Subsequently, 1,008 of the T1 participants (87.42%) completed the depressive symptoms scale and Internet addiction scale 6 months later, in June 2023 (T2).Results(1) Risk perception of COVID-19 was significantly and positively predicted depressive symptoms and Internet addiction 6 months later; (2) Depressive symptoms played a mediating role between risk perceptions and Internet addiction; (3) PTG moderated the first-stage link between risk perception and Internet addiction, and this relationship was more robust for low PTG than for high PTG.ConclusionThese findings advance our understanding of the relationship and mechanisms between risk perception of COVID-19 and Internet addiction, and further support developing interventions to strengthen PTG for mitigating negative outcomes during major crises.